Importance of Phase Change Materials in Heat Transfer Fluids for Solar Heat Absorption - Sudheesh Chandran (International Journal of Energy and Thermal Applications, 2024)
Solar heat absorption involves capturing and storing solar energy for later use. Phase change materials play a crucial role in enhancing the efficiency of heat transfer fluids in solar thermal systems and are integral to the optimization of heat transfer fluids in solar thermal systems. Their ability to store and release thermal energy efficiently, regulate temperatures, and enhance overall system performance makes them a valuable component in the transition towards sustainable and renewable energy sources. This article summarizes that, the use of phase change materials in solar heat transfer fluids is an important way for improving the thermal performance, energy efficiency, and lifespan of a solar thermal system. The paper also discusses about the role of phase change material in heat transfer fluid, the various types of PCMs and the effect of adding various nano particles with PCMs.
Keywords: Phase change materials; Thermal conductivity; microencapsulated phase change materials; nanofluid